Urine Test Accuracy of Lipoarabinomannan in Diagnosing Pulmonary Tuberculosis in Adults: Meta-Analysis - Jihan Nafisah Fauziy; Kartika Febry Ana (Masters Program in Public Health, 2022)
Background: Mycobacterium tuberculosis (Mt) requires non-sputum-based screening that can identify it with high sensitivity and specificity. Lipoarabinomannan (LAM) is a diagnosis of active tuberculosis (TB) in samples such as urine, both by complex laboratory-based testing and in simple treatment tools. The purpose of this study was to determine the accuracy of the Lipoarabinomannan urine test in diagnosing TB in adults. Subjects and Method: This study is a meta-analysis study with PICO covering, population= adult age with suspected tuberculosis (TB). Intervention= lipoarabinomannan urine test. Comparison: no lipoarabinomannan urine test was performed. Outcome: sensitivity and specificity. Using the PRISMA flowchart guidelines. The articles used were conducted between 2012-2021 from the PubMed, Google Scholar, MedLine, and Science Direct databases. The keywords used in the article search were “Lipoarabinomannan” AND “LAM” OR “Adult” AND “Patient” OR “Diagnosis” OR “Pulmonary tuberculosis”. Based on the database, there were 9 articles that matched the inclusion criteria. Data analysis using the RevMan 5.3 application. Results: A total of 9 cohort studies with a total of 3,069 patients from South Africa (Cape Town, KwaZulu-Natal, Zimbabwe), East Africa (Kenya, Malawi, Tanzania, Uganda, Zambia), West Africa (Ghana) and South America (Peru) were selected for the study. systematic review and meta-analysis. A meta-analysis of 9 cohort studies showed that the lipoarabinomannan urine test had 2.89 times the accuracy or sensitivity in diagnosing TB compared to no lipoarabinomannan urine test (aOR= 2.89; 95% CI= 2.30 to 3.63; p= 0.160), but was not statistically significant. Conclusion: The lipoarabinomannan urine test improves accuracy in diagnosing pulmonary tuberculosis in adults but is not statistically significant. Keywords: lipoarabinomannan, LAM, adult, patient, diagnosis, pulmonary tuberculosis. Correspondence: Jihan Nafisah Fauziy. Masters Program in Public Health. Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: jihannafisah321@gmail.com. Mobile: 082135798209.